Representaç\~ao e reforma política: O debate sobre as eleiç\~oes diretas para o Parlasul - Antonio Lassance (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper analyzes the proposals under discussion in the Brazilian Congress concerning the direct elections for Mercosur Parliament (Parlasur), originally planned to be held on 2014. The proposed rules are investigated in order to find out which changes may impact the profile of the new representation to be elected and the consequences by either strengthening or weakening the institutional role of Brazilian representation in Parlasur. Pending electoral legislation for Parlasur may represent the most important experiment in political reform in the country in recent years - changing the open list of candidates to the closed list (with strict party nomination), prohibiting party coalitions, establishing exclusive public financing of campaigns, besides rules targeting gender equality. Notwithstanding, if members of congress do not strengthen reform to provide a more robust institutional framework, Brazilian representation in Parlasur will be weakened rather than strengthened.
Keywords: F53; F55; O19; 330; Mercosur Parliament (Parlasur); political reform; Brazilian political system; Brazilian foreign policy